A Theater Called Spectacle: Phantasmagorical Urban Space in Amit Chaudhuri's A Strange and Sublime Address. Issue 2 (2nd April 2020) - Chakraborty, Sovan; Kumar, Nagendra
Abstract: Urban modernity, since its conceptualization, has been founded on the discourses of what Guy Debord calls "spectacles" or the grand, majestic, decorated expressions of the Imperial/Capitalist progress that signify a modern metropolis. These spectacles, both physically and metaphysically, represent the vast accumulation of commercial, cultural and intellectual wealth, meant for sensualizing an audience. In many cases, on contrary, they produce a psychopathology, what George Simmel calls a blasé attitude, marked by indifference, irritation and superficiality. A flâneur is a significant example of this urban type, whose gaze is symptomatic of the spirit of an ascetic roaming in the jungle of concrete. This very often incisively dissects the progressive dicta of an "advanced" metropolis to lay bare its dark and hidden crevices, hitherto unknown or unnoticed. S/he thus creates a new esthetic of urban writing by exploring the non-spectacular and banal spatio-temporality of the city (the "trash of history") and catching the inevitable ambiguities as if in flashes of what Benjamin calls the "dialectical images." This paper proposes to look at this alternative dialectical vision of urban modernity through Amit Chaudhuri's celebrated fiction A Strange and Sublime Address (1991). The arguments made in the paper move chiefly around three topics: theoretical exploration of the dialectical character of spectacle and phantasmagoria in context of modern urban space, and the treatment of these theories in analyzing the fiction with the help of the concepts like the "dialectical image" and the simultaneous "now-time" or " Jetztzeit "; situating the novel in the cultural-historical and socio-political milieu during and after the liberalization of Indian economy in 1991, especially from the author's perspective; and analyzing alternative narrative strategies employed in the novel by means of cloze reading.